Dye-conjugated upconversion nanoparticles for ratiometric imaging of intracellular pH values. Issue 26 (8th June 2015) - Ma, Tingchun; Ma, Yun; Liu, Shujuan; Zhang, Lili; Yang, Tianshe; Yang, Hui-Ran; Lv, Wen; Yu, Qi; Xu, Wenjuan; Zhao, Qiang; Huang, Wei
Abstract : An xylenol orange-functionalized upconversion nanoprobe has been developed, which can be used for ratiometric upconversion luminescence bioimaging of intracellular pH changes. Abstract : A ratiometric pH probe based on Tm 3+ doped UCNPs functionalized with dye xylenol orange on the surface was developed, which can realize ratiometric pH sensing and imaging under continuous-wave excitation at 980 nm through the quenching and recovery of upconversion luminescence at 450 nm from UCNPs.